**i.** 3x + 12 = 2x – 4

∴ 3x + 12 – 12 = 2x – 4 – 12

**…[Subtracting 12 from both the sides] **

∴ 3x = 2x – 16

∴ 3x – 2x = 2x – 16 – 2x

**…[Subtracting 2x from both the sides] **

∴ x = – 16

**ii.** 5 (x – 3) = 3 (x + 2)

∴ 5x – 15 = 3x + 6

∴ 5x – 15 + 15 = 3x + 6 + 15

**…[Adding 15 on both the sides] **

∴ 5x = 3x + 21

∴ 5x – 3x = 3x + 21 – 3x **…[Subtracting 3x from both the sides] **

∴ 2x = 21

\(\therefore \cfrac{2x}{2} =\cfrac{21}{2}\) **…[Dividing both the sides by 2]**

∴ x = \(\cfrac{21}{2}\)